Expansive intracardiac leiomyosarcoma - a combined therapeutic approach resulting in survival with complete remission. A literature review and case report - Jan Juchelka; Martin Simek; Pavel Marcian; Jiri Ehrmann; Petr Santavy (Biomedical Papers, 2023)
Primary cardiac sarcomas are extremely rare and often with dismal prognosis. Only a few case series and retrospective studies regarding its biological characteristics, diagnostics, and treatment were reported. The multi-modality therapeutic strategy has been discussed in the published literature, but often with contradictory results. There is thus, no consensus on the optimal therapeutic approach to date. We present the case report of the 66-year old female endangered by a large primary leiomyosarcoma expanding in the right-sided heart chambers with imminent risk of acute obstruction of blood flow. The patient was managed by urgent surgical resection. After the histological confirmation of incomplete R1 resection, the treatment was supplemented by adjuvant CT-targeted radiotherapy, resulting in extraordinary survival with complete remission over a 24-month follow-up period. Our case report aims to demonstrate a favorable result of an individually suited complex surgical and oncological treatment to support the multidisciplinary therapeutic approach to these patients. The article is supplemented by a detailed literature review providing a theoretical background and an overview of the acquired knowledge and possible strategies.